Current State of the Level of Teachers’ Awareness Regarding SocialPedagogical Support for Students: Analysis of Findings - Dvornyk, O.; Ruban, N. (Problems of Engineer-Pedagogical Education, 2023)
This article addresses the intricate challenges confronting education in the wake of reforms, societal digitalization, and exceptional circumstances like quarantine measures and the full-scale war. It highlights the significance of incorporating social-pedagogical support into education, especially in the midst of educational modernization. The research delves into scholarly sources to explore diverse facets of social-pedagogical support for students and its influence on the development and social adaptation of children. Based on the findings of sociological studies, the article determines the current level of awareness among educators teaching 5-11 grade kids about social-pedagogical support. The article investigates educators who have been performing or performed the duties of a homeroom teacher throughout their pedagogical careers and their contributions to implementing social-pedagogical support within general secondary education settings. It identifies the importance of the presence of social pedagogues at schools and their role in rendering social-pedagogical assistance. Moreover, the research examines the way teachers comprehend pivotal terms tied to socialpedagogical support for students, including "social protection of children at schools," "challenging life circumstances," "social-pedagogical support," factors contributing to difficult situations with children, and more. The paper enumerates the adverse outcomes stemming from educators’ limited competence in the field of child social protection within schools. It investigates teachers’ understanding of their functional responsibilities in the realm of social protection and its influence on the quality provision of social-pedagogical support. Furthermore, the study probes educators’ grasp of their responsibility in recognizing students undergoing challenging life circumstances. The number of educators who have encountered cases of bullying in general secondary education institutions is indicated. Conclusions are drawn, highlighting the imperative of elevating educators’ awareness regarding social-pedagogical support for students.